Rancang Bangun Sistem Informasi Kependudukan dan Pelayanan Masyarakat Desa Sopet Kecamatan Jangkar Kabupaten Situbondo - Mahendra, Yusril Haza; Baijuri, Acmad; Santoso, Firman (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
This study aims to develop a population information system application and village services to improve population administration data processing in Sopet Village, Jangkar District. The village is currently still using manual paper forms in the population service process, which are prone to data loss and corruption. In this study, researchers designed and developed an application that allows easy access to population information and improves the efficiency of public services. The application development method involves the stages of needs analysis, system design, software development, and application testing. The application includes fast data retrieval features, secure data storage, and the ability to generate reports efficiently. In the long term, it is expected that this application will enhance the efficiency of population administration, reduce the risk of data loss or damage, and contribute to the improvement of village governance. This research has important implications for population administration at the village level. The implementation of this application is expected to serve as a model for other villages to adopt information technology, thereby enhancing the quality of population services and promoting development at the village level